Lessons From COVID-19: Physical Exercise Can Improve and Optimize Health Status - Cerasola, Dario; Argano, Christiano; Corrao, Salvatore (Frontiers in Medicine, 2022)
The outbreak of Coronavirus Disease 2019 (COVID-19) has caused increasing challenges for healthcare systems globally. The disease spread rapidly from Wuhan to the rest of the world, involving more than 400 million individuals and including more than 5 million deaths. In dealing with the pandemic, China and other countries took protective measures such as promoting social distancing, canceling public gatherings, closing schools, quarantining, and imposing lockdowns. All these measures lead to physical inactivity. Being physically inactive has significant repercussions on the status of physical and mental wellbeing, and it is associated with anxiety, stress, increased chronic disease risk, and worsening of chronic conditions. In this sense, the relevance of maintaining a healthy lifestyle through physical exercise has been outlined by the World Health Organization (WHO). The aim of this mini review is to discuss the importance of physical activity in the context of the COVID-19 pandemic, highlighting the benefits of physical activity and exercise that could be potentially effective treatment strategies for comorbid chronic conditions, long covid syndrome (LCS), and symptoms such as depression and anxiety.